A Comparative Study on the Sensitivity of D-Dimer with Doppler ultrasound in the Diagnosis of Deep Venous Thrombosis - Aneza Jalil, Muhammad Azeem Khan, Ahmed Farhan, Ana Jalil, Hira Jalil, Farogh Elahi, (Journal of Rawalpindi Medical College, 2022)
Introduction: Deep venous thrombosis (DVT) is a coagulation disorder that is on the rise due to lifestyle changes. Patients with DVT are at risk for developing a life-threatening complication, pulmonary embolism which urges the importance of its early diagnosis. The Gold standard modality for its early diagnosis is invasive which is Venography. Other modalities like compression ultrasound and duplex imaging are noninvasive but operator-dependent and not routinely available during evening and night shift hours. D-Dimer is a simple, noninvasive, cost-effective, and easily available diagnostic test that can be helpful in diagnosis. The objective of this study is to compare the sensitivity of D-Dimers with Doppler ultrasound for the diagnosis of deep venous thrombosis. Materials and Methods: A cross-sectional comparative (validation) study in which 65 admitted patients with a high risk of DVT on Well’s criteria for clinical diagnosis were enrolled by non-probability convenience sampling from March to August 2018. Both D-Dimer and Doppler ultrasounds were performed on all suspected patients of DVT. Results: Amongst 65 cases, 60 (92.3%) had positive Dimer results compared to 65 (100.0%) with the Doppler ultrasound. The difference between the two diagnostic modalities was statistically significant (p-value = 0.02). The sensitivity of D-dimers was 92.3% however specificity, PPV, and NPV were 0% as none of the cases was negative on ultrasound Doppler. Conclusion: The D-dimer test is a conveniently performed, cost-effective test with a sensitivity of more than 90% in the current study and can be useful for Emergency and critical care departments.